High impact management techniques for any project. - Voegtli, Cinda (IEEE Antennas & propagation magazine.)
One does not have to go to days and days of classes to gain important know-how for managing your projects. While aspects of project management are important-work-breakdown structures, scheduling techniques, and project communication among others-a few key techniques can be implemented easily, and bring some huge leverage for finishing projects successfully. This paper offers practical project management "tools" that you-as a project manager, functional manager, or team member-can use immediately. It covers project visions and risk ranking for early testing, and illustrates best practices from other internal and external project teams.